Pengaruh Kondisi Keuangan dan Kondisi Pajak terhadap Cost of Debt - Merdhania Khusumaningrum; Nuramalia Hasanah; Hera Khairunnisa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study analyzes the effect of financial conditions and tax conditions on the cost of debt. The financial conditions in this study are firm size, capital structure, and profitability. The tax conditions in this study are tax avoidance and tax risk. The analysis technique used in this study is panel data regression analysis and processed using EViews version 13. The population in this study were Hotel, Restaurant and Tourism industry companies for the 2018-2022 period which were selected using the purposive sampling method and a sample of 135 was obtained over 5 years. The results of this study shows that firm size has an effect on the cost of debt. Meanwhile, capital structure, profitability, tax avoidance and tax risk have no effect on the cost of debt.